Significance of nickel particles on reducing friction and wear of polyimide subjected to harsh boundary lubrication conditions. (February 2023) - Lin, Yusong; He, Ren; Xu, Yongkun; Zhang, Jianjun; Wetzel, Bernd; Zhang, Ga
Abstract: Nickel (Ni) particles were compounded into polyimide (PI) and PI reinforced with carbon fiber (CF). Role of Ni particles on tribological performance of the PI-based materials sliding against a bearing steel were investigated under boundary and mixed lubrication regimes. Remarkably, PI composites filled with Ni exhibit ultra-low friction and wear. Interestingly, friction- and wear-reduction roles of Ni are much more significant than those of CF. The results provide direct evidence that an extremely thin NiO glaze layer grows on the steel counterface, above which a uniform C-based tribofilm is formed. It is assumed that the NiO layer can catalyze dehydrogenation of oil molecules and promote tribofilm formation. The present work proposes a design concept of high-performance tribofilm for improving boundary lubrication of motion components. Highlights: Ni particles were compounded into PI and CF-reinforcing PI. Ni greatly improve tribological performance of PI composites under harsh lubrication conditions. Friction- and wear-reduction roles of Ni are much more significant than those of CF. A thin NiO glaze layer grows on steel counterface, which can promote tribofilm formation.